2014
DOI: 10.1038/aps.2014.1
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate transporters in brain ischemia: to modulate or not?

Abstract: In this review, we briefly describe glutamate (Glu) metabolism and its specific transports and receptors in the central nervous system (CNS). Thereafter, we focus on excitatory amino acid transporters, cystine/glutamate antiporters (system x c -) and vesicular glutamate transporters, specifically addressing their location and roles in CNS and the molecular mechanisms underlying the regulation of Glu transporters. We provide evidence from in vitro or in vivo studies concerning alterations in Glu transporter exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 232 publications
(295 reference statements)
0
51
0
Order By: Relevance
“…This observation seems to be common in several previous reports, where it was observed that the high K + stimulus produces a rise in Glu content, but also falls while the stimulus is still present . Extracellular levels of Glu are controlled by four types of high‐affinity, sodium‐dependent glutamate transporters: GLAST and GLT‐1, localized primarily in astrocytes, EAAC1, widely distributed in neurons, and EAAT4 localized principally in cerebellar Purkinje cells . GLT‐1 is responsible for uptake up 90% of the total Glu, being a relevant factor the enzyme glutamine synthetase, which converts Glu into glutamine inside of astrocytes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation seems to be common in several previous reports, where it was observed that the high K + stimulus produces a rise in Glu content, but also falls while the stimulus is still present . Extracellular levels of Glu are controlled by four types of high‐affinity, sodium‐dependent glutamate transporters: GLAST and GLT‐1, localized primarily in astrocytes, EAAC1, widely distributed in neurons, and EAAT4 localized principally in cerebellar Purkinje cells . GLT‐1 is responsible for uptake up 90% of the total Glu, being a relevant factor the enzyme glutamine synthetase, which converts Glu into glutamine inside of astrocytes .…”
Section: Discussionmentioning
confidence: 99%
“…[43] Extracellular levels of Glu are controlled by four types of high-affinity, sodium-dependent glutamate transporters: GLAST and GLT-1, localized primarily in astrocytes, EAAC1, widely distributed in neurons, and EAAT4 localized principally in cerebellar Purkinje cells. [44] GLT-1 is responsible for uptake up 90% of the total Glu, [45] being a relevant factor the enzyme glutamine synthetase, which converts Glu into glutamine inside of astrocytes. [46] We (data not published) and others have observed astrogliosis as a long-term response before an early hypoxic event.…”
Section: Discussionmentioning
confidence: 99%
“…; Krzyżanowska et al . ). NMDA receptors, which play an important role in synaptic development, and learning and memory, are found throughout the brain (Monyer et al .…”
Section: Excitotoxicity and Nmda Receptorsmentioning
confidence: 97%
“…Most studied neuroprotectants for the treatment of stroke have targeted the DL-a-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) receptor and the NMDA receptor, which are glutamate-activated ion channels (Besancon et al 2008;Krzy_ zanowska et al 2014). NMDA receptors, which play an important role in synaptic development, and learning and memory, are found throughout the brain (Monyer et al 1994;Sanz-Clemente et al 2013).…”
Section: Excitotoxicity and Nmda Receptorsmentioning
confidence: 99%
“…Although many neuroprotective agents protected against neuronal damage in cerebrovascular diseases, few neuroprotective agents are effective in vivo due to neglecting the correlation of multiple biological injuries of ischemia. [3][4][5] Therefore, it became a hot topic about novel neuroprotective agents in ischemia via intervening in multiple pathways.…”
Section: Introductionmentioning
confidence: 99%